CENTRALISTIC REFORM: A CRITICAL DISCOURSE ANALYSIS OF TAX REFORM CAMPAIGN IN THE DIRECTORATE GENERAL OF TAXES - Tri Juniati Andayani; Ratih Puspa; Henri Subiakto (Profetik: Jurnal Komunikasi, 2021)
The Directorate General of Taxes (DGT) has been running a tax reform program to enable a comprehensive transformation in the taxation system to create a strong, credible, and accountable tax institution. This program enhances equitable taxation and an excellent and integrated data expansion to increase tax revenues. The discourses on tax reform are primarily promoted on DGT communication channels, including its online social media. This discourse leads to a likely impact of a partial taxation system. Thisresearch aims to analyze the discourse of tax reform on the online social media of DGT using Norman Fairclough’s Critical Discourse Analysis based on texts on online media as the primary data. It was revealed that DGT conveys messages about tax reform in three ways: tax reformation as a public communication campaign, discourse of Indonesia taxation transparency, and discourse of taxation in the Directorate General of Taxes to face the 4.0 industrial revolution. DGT conveys these three discourses according to its work scope as a state institution that constantly strives for making transformations through its programs that are carried out based on the provisions of the umbrella institutions, including the vision and mission of the President. In this case, the President’s vision and mission are inseparable from the demands of the times, international pressure, the history of the nation, and social changes in society.